Opportunities for Parallel Import in China (Shanghai) Pilot Free Trade Zone: Evidence from the Automobile Industry and the Pharmaceutical Industry - Wu, Maoguo; Yan, Siyuan (European Scientific Journal, ESJ, 2018)
Parallel import, as a pattern of international trade, is often under criticism because of infringement of intellectual property. However, the establishment of China (Shanghai) Pilot Free Trade Zone has contributed to the rapid development of parallel import, which has existed in the “grey zone” in China for a long time. Generally speaking, parallel import not only minimizes damages to related intellectual property owners, but also maximizes flow of goods and promotes formation of a unified market, which is beneficial to free trade and economic integration as well as the welfare of consumers. This paper investigates two industries most affected by parallel import, namely the automobile industry and the pharmaceutical industry. Two cases, “Peugeot Unfair Competition” and “Compulsory Licensing of the Indian Pharmaceutical Industry”, are analyzed. This paper draws the conclusion that the general welfare of society must be considered and a clear boundary of intellectual property rights should be established in the development of trade policies on parallel import. Effective use of parallel import can ultimately promote social development.